Physical Activity, Rehabilitation and Health Education in High-Risk Patients: Lessons from Vascular Ehlers–Danlos Syndrome - Ryszkowska, Kamila; Krzyżowska , Kinga; Perzyńska, Jagienka; Pawelec, Natalia; Podkościelna, Jaśmina; Bagińska, Weronika; Załuska, Urszula; Purska, Aleksandra; Grabiński, Jakub (Quality in Sport, 2026)
Background. Physical activity is a fundamental component of health, prevention, and education; however, in selected high-risk populations, safe exercise prescription remains a major challenge. Vascular Ehlers–Danlos syndrome (vEDS) represents an extreme model of exercise-related risk due to marked vascular fragility. Aim. The aim of this study was to analyse the safety of physical activity in vEDS and to provide practical implications for sport participation, rehabilitation, and health education. Material and methods. A narrative review of available literature was performed, focusing on exercise- and sport-related complications, rehabilitation practices, and current recommendations for physical activity in patients with vEDS. Results. Analysis of reported cases shows that both competitive sports and low-intensity activities, including standard rehabilitation exercises, may trigger severe and potentially fatal vascular events. At the same time, appropriate low-load, supervised physical activity may support functional capacity and quality of life. Current recommendations are inconsistent and largely based on expert opinion, leading to uncertainty among patients and professionals responsible for exercise guidance. Conclusions. The findings highlight the need for a structured, education-based approach to physical activity in high-risk populations. In vEDS, exercise prescription should prioritise safety, individualisation, and professional supervision. The development of clear guidelines and improved education of clinicians, physiotherapists, and sport practitioners is essential to ensure safe participation in physical activity while minimising the risk of serious complications.